MicroRNAs as Biomarkers for Nephrotic Syndrome - Tsuji, Kenji (Int J Mol Sci, 2020)
Nephrotic syndrome represents the clinical situation characterized by presence of massive proteinuria and low serum protein caused by a variety of diseases, including minimal change nephrotic syndrome (MCNS), focal segmental glomerulosclerosis (FSGS) and membranous glomerulonephropathy. Differentiating between diagnoses requires invasive renal biopsies in general. Even with the biopsy, we encounter difficulties to differentiate MCNS and FSGS in some cases. There is no other better option currently available for the diagnosis other than renal biopsy. MicroRNAs (miRNAs) are no-coding RNAs of approximately 20 nucleotides in length, which regulate target genes in the post-transcriptional processes and have essential roles in many diseases. MiRNAs in serum and urine have been shown as non-invasive biomarkers in multiple diseases, including renal diseases. In this article, we summarize the current knowledge of miRNAs as the promising biomarkers for nephrotic syndrome.